AN INTRODUCTION TO SISTEM IDENTIFICATION FOR A QUARTER CAR PASSIVE SUSPENSION - Endang Susanti (Universitas Riau Kepulauan, 2016)
At present, as a method of establishing mathematical model of the system, the system identification has been widely applied to the automatic control, aviation, spaceflight, astronomy, medicine, biology, marine ecology and society, economics and many other fields. With the rapid development of science and technology, the status of system identification technique in various disciplines is becoming increasingly important. This paper introduces an system identification used for a quarter car passive suspension and a review previous research.